KONSUMSI BAHAN KERING DAN KECERNAAN CALCIUM, PHOSPHOR PAKAN LOKAL DAN IMPOR PADA ANAK KUDA PACU INDONESIA - Nangin, Gabriela; Tulung, Y.L.R.; Tuturoong, R.A.V.; Rumambi, A. (Universitas Sam Ratulangi, 2020)
DRY MATTER CONSUMPTION AND THE DIGESTIBILITY OF CALCIUM AND PHOSPHORUS IN BOTH LOCAL AND IMPORTED FEED FOR RACER FOAL OF INDONESIA. The purpose of this study to determine the ability of foal to the consume and digest both local feed and imported feed. This study was carried out in the Pinabetengan village, Tompaso district, for 30 days During these days preparation and data collection was carried out. The object of the study was the foal’s feed, either the amount or the type of it, and the foal’s feces. There were seventeen foal’s for the object of this study. Divided into two groups. First group contained nine foal’s consuming local feed and the other group contained eight foal’s consuming imported feed. The variable measured was the digestibility Ca and P. The study analyzed statistically using t-Test method: Two- Sample Assuming Unequal Variances. The result of this study using t-Test method indicated that the digestibility Ca of imported feed 1.22 0.82 was significantly higher p<0,05 than the local feed, as well as in the digestibility P of import feed 0,68 0,56. Based on the result of this study, it can be concluded that the digestibility of Ca and P for imported feed is better than the digestibility of Ca an P for local feed.Keywords: Racer foal, Local feed, Imported feed, Digestibility of Ca dan P